A Rare case of Sanfilippo syndrome type “C” - Agarwal, Ansh; Goyal, Kashish; Mathur, Priyanshu; Mathur, Avisha (Indian Journal of Child Health, 2020)
Sanfilippo syndrome or mucopolysaccharidosis type III is a rare autosomal recessive neurodegenerative lysosomal storage disease. The prevalence of Sanfilippo syndrome is 1 in 100,000 live births. Here, we are presenting a case of an 8-year-old female child who presented with mild intellectual disability, sleep deprivation, and hyperactivity. The patient was diagnosed with Sanfilippo syndrome type C. The diagnosis was made by increased heparan sulfate in urine analysis and exome sequencing showed homozygous missense variant c.1622>T (p.Ser541Leu) in exon 17 of HGSNAT gene that leads to amino acid substitution from serine to leucine at codon 541. We are presenting this case because several diseases have similar clinical presentation and there is difficulty in making definitive diagnosis. The importance of early diagnosis is to prevent complications and recurrence of the disease in subsequent pregnancies.